Accumulation of sodium and manganese during litter decomposition of Qinghai spruce (Picea crassifolia) forest in China - Xinning Zhao; Fei Zang; Fangyuan Huang; Na Li; Chuanyan Zhao (Ecosphere)
Abstract Litter decomposition is a key ecological process as a control on nutrient cycling in forest ecosystems. Forest litter is an important carrier of element cycles in forest ecosystems. The biogeochemical cycle of elements is of great significance to plant communities and ecosystem functions. At present, most of the studies on the litter major elements have focused only on C, N, and P, and there are few studies on the biogeochemical cycle of sodium (Na) and manganese (Mn) of forest litter. In this study, we investigated the concentrations and fluxes of Na and Mn in needle litter of Qinghai spruce over a 12‐month period. We measured the release and accumulation dynamics of litter Na and Mn during litter decomposition at different canopy coverage and elevations over 3.9 years. The results show that the annual Na and Mn concentrations were 312.34 and 621.19 mg kg−1, and the annual fluxes of Na and Mn were 236.67 and 343.16 g ha−1 in needle litter, respectively. After 3.9 years of litter decomposition, Na released 15.6% and Mn accumulated 93.4% compared to the initial concentration. The concentration of Na and Mn in needle litter both accumulated fastest at low canopy coverage. The concentrations of Na and Mn were different at various elevations, but there was no obvious regularity. These results illustrate the seasonal characteristics of litter element return and nutrient cycling during litter decomposition in typical coniferous forests in the Qilian Mountains and could provide basic data and theoretical basis for ecological protection in the Qilian Mountains.